2015
DOI: 10.3390/su7032437
|View full text |Cite
|
Sign up to set email alerts
|

Low Carbon Urban Transitioning: From Local Experimentation to Urban Transformation?

Abstract: Abstract:Climate change mitigation remains a contested political and policy issue nationally in Australia. Nevertheless, Australian cities have been actively engaging with low carbon policy for well over a decade and numerous actions and programs have resulted. A question arises as to whether such initiatives can amount to a transition; a systemic change from one dominant fossil-fuel based socio-technical regime, to another, fossil-free based socio-technical regime. In this paper, we review the critical litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(41 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…This perspective encapsulates the view of those undertaking local experimentation, including non-scientists, as a new form of societal knowledge production, emphasizing a feedback cycle of development, testing, evaluation and informing best practice management [16], or foresight, experimentation and learning in the management of societal transitions [22,23]. Experiments in this line of thought support learning about the possibilities and problems of new governance structures, or new technologies from a governance perspective.…”
Section: Conceptual Approaches To Learning In Pilot Projects and Demomentioning
confidence: 99%
“…This perspective encapsulates the view of those undertaking local experimentation, including non-scientists, as a new form of societal knowledge production, emphasizing a feedback cycle of development, testing, evaluation and informing best practice management [16], or foresight, experimentation and learning in the management of societal transitions [22,23]. Experiments in this line of thought support learning about the possibilities and problems of new governance structures, or new technologies from a governance perspective.…”
Section: Conceptual Approaches To Learning In Pilot Projects and Demomentioning
confidence: 99%
“…Initiating further comprises stakeholder involvement (Burch et al 2014; Moloney and Horne 2015) and policy formation (Burch et al 2014). Studies of urban climate governance have empirically demonstrated significant variation in the degree of institutionalization in the policy developed (Burch et al 2014; Nevens and Roorda 2014; Moloney and Horne 2015; Wolfram 2016).…”
Section: Developing the Assessment Framework And Evaluating Its Influmentioning
confidence: 99%
“…is by Susie Moloney and Ralph Horne [9]. The authors look at the Australian case of the city of Melbourne, and argue that climate change mitigation remains a contested political and policy issue.…”
Section: Achieving Better Urban Precinctsmentioning
confidence: 99%